Morphological and Histological Structure of Eye in Lizard Hemidactylus flaviviridis - Azhaar R. Al –Fartwsy (Journal of Madenat Alelem University College, 2016)
The aim of the present study is to determine the anatomical and histological structure of the eye in lizard Hemidactylus flaviviridis (House gecko). The results show that eye located dorsolateral in the head and spherical, with elongated oval pupil. Histologically, it is composed of eyeball, lens and optic nerve. It is lack eyelid thus it was covered by external Tertiary spectacles. The eyeball appeared surrounded by three tunical they are from the inside to the outside tunica interna, tunica media, tunica fibrosa. The tunica interna consist of the retina,and the retina composed of eight layers and two membranes are from outer to inner, the pigment epithelial layer, photoreceptor layer (rods and cones layer), this layer showed one type of cones and two types of rods that were the single, double rods. External limiting membrane, outer nuclear layer, outerplexiform layer, inner nuclear layer, inner plexiform layer, ganglion cell layer, nerve fibers layer, internal limiting membrane, one dorsal central fovea also appeared in retina. The tunica middle composed from choroid, ciliary body, iris, the ciliary body appeared with ciliary processes and unbranched, while the iris appeared hierarchical or triangular. The fibrous tunica consists of sclera which supported by hyaline cartilage in the hemisphere rear eye. The anterior part of the tunica formed cornea which divided in to central cornea and peripheral cornea. Key words: Eyeball, Retina, Photoreceptor, Lizard (House Gecko)